Pemodelan Spasial Daerah Rawan Kebakaran Hutan dan Lahan Pada Kabupaten Karo Menggunakan Metode Analytical Hierarchy Process - Muhammad Amsyar Koedadiri; Agus Purwoko; Nurdin Sulistyono (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Karo Regency is in the Bukit Barisan range and most of its area is upland and riverine, and there are two active volcanoes. Forest and land fires are an important issue to pay attention to because of their impact on the e nvironment, especially in Karo Regency because of its huge potential for nature tourism development. Geographic Information Systems (GIS) and Analytical Hierarchy Process (AHP) are used to identify vulnerable areas. The aim of this research is to identify vulnerable areas in Karo Regency. The results of this research show that an area of 102,598.04 ha (46.94%) is in the very high vulnerability category, 52,771.26 ha (24.14%) is in the high category, 39,220.70 ha (17.94%) is in the medium category, 22,069.91 ha (10.10%) is in the low category and 1,931.27 ha (0.88%) is in the very low category. A total of 293hotspots are in very high vulnerability areas. 208 hotspots are in areas with a high level of vulnerability, 131 hotspots have a medium level of vulnerability and 27 hotspots have a low level of vulnerability.